The Role of Cooperatives in Improving Members' Welfare at Fishermen Cooperatives in Abeli District, Kendari City - Nur Anisha; Abdul Gafaruddin; Fahria Nadiryati Sadimantara (International Journal of Technology and Education Research, 2024)
This research aims to find out the role of cooperatives in improving the welfare of members in cooperatives in Abeli District, Kendari City, the obstacles faced by cooperatives in improving the welfare of members in cooperatives in Abeli District, Kendari City, and the strategies used by cooperatives in facing various obstacles in their efforts to improve members' welfare at a cooperative in Abeli District, Kendari City. This research was carried out in Abeli District, Kendari City. The subjects of this research were cooperative leaders, cooperative managers and cooperative members using purposive sampling techniques. The variables in this research are the identity of the respondent and the role of the cooperative. The analysis used is qualitative analysis. The results of this research show that 1) the role of cooperatives in improving members' welfare, namely providing loans, providing entrepreneurial training, providing job opportunities. 2) the obstacles are providing loans (limited capital owned by fishermen's cooperatives, lack of awareness of loans in a cooperative business unit and lack of collateral owned by fishermen), places for entrepreneurship training (limited financial resources and inadequate infrastructure), providing job opportunities (limited capital, skills and qualifications of the workforce). 3) Strategies faced in improving members' welfare, namely providing loans (limited capital owned by fishing cooperatives, lack of awareness in a cooperative unit, lack of collateral in providing credit loans), entrepreneurship training places (limited financial resources and inadequate infrastructure), providing employment opportunities (limited capital, skills and qualifications of the workforce).